Peduli Ibu Rumah Tangga Melalui ‘Gesini” (Gerakan Deteksi Dini) Tb Anak Di Wilayah Surabaya Berbasis Kearifan Lokal - Sari, Ethyca; Aristina Halawa; Dewi Perwita Sari; Dianita Primi Hastuti (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2025)
Tuberculosis is an infectious disease, childhood TB occurs due to attacks by Mycobacterium Tuberculosis bacteria in the lungs and is a disease that can be cured and is not a hereditary disease. However, currently TB cases in Indonesia are still relatively high and Indonesia is ranked second after India. Children are an age that is very vulnerable to the transmission of Tuberculosis. The transmission rate and danger of transmission are high in the 0 - 6 year age group and the 7 - 14 year age group. The aim of this Community Service is to increase the knowledge and abilities of housewives through "GESINI" as an effort to assist in preventing the increase in pulmonary TB through activities for early detection of TB in children. The method of implementing this activity includes preparation, data analysis, planning, implementation and evaluation of activities. The results of the implementation showed that the knowledge of housewives when the pretest knowledge was carried out was at a poor level, after being given the training material, a post test was carried out showing that the majority had a good level of knowledge. When housewives carry out direct implementation in the community, most of the results show that they are correct in carrying out both data studies and assessing TB scoring in children, so it can be said that the implementation of Caring for Housewives training through "GESINI" (Early Detection Movement) for Children's TB In the Surabaya area based on local wisdom, it can be implemented well and run smoothly. It is hoped that this activity can be carried out continuously and made into a program in the Putat Jaya Subdistrict RW, so that the knowledge of all communities in the area will be better about this TB disease.